Bank Capital and Lending Relationships - SCHWERT, MICHAEL (Journal of Finance, 2018)
ABSTRACT This paper investigates the mechanisms behind the matching of banks and firms in the loan market and the implications of this matching for lending relationships, bank capital, and credit provision. I find that bank‐dependent firms borrow from well‐capitalized banks, while firms with access to the bond market borrow from banks with less capital. This matching of bank‐dependent firms with stable banks smooths cyclicality in aggregate credit provision and mitigates the effects of bank shocks on the real economy.